About the ‘Cape’. Considerations on Geometries of the Maurizio Sacripanti’s Osaka Pavilion Roof (diségno, 2018)
This study focuses on the interpretation of the shape of double curvature surfaces, which characterize the morphology of unrealized architectural projects, particularly interesting from the point of view of shape. The analysis of architecture, carried out by means of analogical instruments proper of the tradition of drawing, today finds a fruitful experimentation field in digital space and a privileged place for studying and validating the geometrical properties of architectural shape.The experimented methodology faces the problem of reading architectural surfaces through the control of the respective geometrical properties in the field of continuous tridimensional representation in digital space. The object of the experimentation is the covering of the pavilion designed by Maurizio Sacripanti for the Universal Exposition of Osaka in 1970. It is an emblematic case because of the different interpretations to which the drawings of the ‘cape’ are susceptible.Moreover, the interest for this work regards both the geometrical shape of the roof and the idea of movement, which becomes the backbone of a kinetic architecture that transforms technology into architectural language.
Keywords: Maurizio Sacripanti; Italian pavilion; kinetic architecture; Osaka; Cape